2VO as affordable model for neurodegeneration- IIUM experience - Allow, Ahmed Kaid Naji (2018)
Reduced cerebral blood flow to the brain tissue is usually associated with cognitive weakening in aging people and can lead to development of neurodegenerative disorder pathologically similar to Alzheimer’s disease. While an accidental interruption of the cerebral blood circulation (acute) can lead to the clinicopathological disorder called stroke, the gradual reduction of cerebral blood flow impairs memory processes and culminates in the appearance of dementia manifested by both neurological and psychiatric. Permanent bilateral ligation of the common carotid arteries, also known as 2 vessel occlusion (2VO), has been established as a model to investigate the effects of chronic cerebral hypoperfusion on development of neurodegenerative processes. There are several phases that follow 2VO. The acute phase takes place during the first 2-3 days after operation. In this phase, reduction of cerebral blood flow can reach up to 50%. In the chronic phase, which extends to 10-12 weeks after 2VO operation, the neurodegeneration has already happened but the cerebral blood flow might be back to normal. In this session of Neuroscience Symposium-II 2018, we will talk about IIUM/KOM/BMS experience regarding 2VO as an animal model of neurodegeneration. Some of the research projects that were done in BMS over the past few years will be presented focusing on work published by our Master and PhD students in indexed peer-reviewed journals. One of the PG students will demonstrate his experience with 2VO. Based on the IIUM/KOM/BMS experience, the difficulties encountered in performing 2VO and the survival rate of adult rats that have undergone the procedure will be highlighted too.